2020
DOI: 10.1016/j.cub.2020.05.079
|View full text |Cite
|
Sign up to set email alerts
|

Release and targeting of polycystin-2-carrying ciliary extracellular vesicles

Abstract: Extracellular vesicles (EVs) are emerging as a universal means of cell-to-cell communication and hold great potential in diagnostics and regenerative therapies [1]. An urgent need in the field is a fundamental understanding of physiological mechanisms driving EV generation and function. Ciliary EVs act as signaling devices in Chlamydomonas and C. elegans [2-4]. Mammalian cilia shed EVs to eliminate unwanted receptors [5] or to retract cilia before entering the cell cycle [6]. Here we used our established C. el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…C. elegans EV-releasing cilia are specialized structurally and functionally. The cilia of C. elegans EV-releasing neurons (EVNs) protrude to the environment from cuticular pores 2527 and shed EVs in response to mechanical pressure 28 . EVN ciliary membrane homeostasis of PKD-2 is modulated by a phosphoinositide 5-phosphatase 29 and caveolin 30 .…”
Section: Discussionmentioning
confidence: 99%
“…C. elegans EV-releasing cilia are specialized structurally and functionally. The cilia of C. elegans EV-releasing neurons (EVNs) protrude to the environment from cuticular pores 2527 and shed EVs in response to mechanical pressure 28 . EVN ciliary membrane homeostasis of PKD-2 is modulated by a phosphoinositide 5-phosphatase 29 and caveolin 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that only a subset of ciliary proteins enters the C. elegans male EVs (21,25). To explore which cilia proteins can enter basal ectosomes to be exported to the embedding glial cells, we fluorescently tagged several ciliary membrane proteins endogenously expressed in AFD, ASER and ASK neurons and known to localise to their cilia.…”
Section: Endogenous Ciliary Receptors Are Sorted To Ectosomes and Expmentioning
confidence: 99%
“…In C. elegans, the polycystin-2 ortholog PKD-2 localises to the cilia of a subset of male ciliated sensory neurons (20). These male ciliated neurons were shown to release PKD-2-containing EVs into the external environment, where they contribute to interindividual communication (17,21). Electron microscopy of the male cephalic sensilla revealed EVs accumulating in the lumen surroundings of the cilia base of male cephalic neurons (CEM neurons), hinting for a release at the ciliary base (17).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the cellular context, EVs can contain beneficial or pathogenic cargos that, for example, promote wound healing or neurodegeneration (Raposo & Stoorvogel, 2013). Traditionally considered receivers of signals, cilia can also release signals in the form of extracellular vesicles (EVs), and the green alga Chlamydomonas reinharditii and C. elegans have offered insights into the contents, function, biogenesis, and release of ciliary EVs (Akella et al., 2020; Cao et al., 2015; Luxmi et al., 2019; Maguire et al., 2015; O'Hagan et al., 2017; Silva et al., 2017; Wang et al., 2014, 2015; Wood et al., 2013); Wang et al., 2020).…”
Section: Extracellular Vesicle (Ev) Releasing Abilities Are Limited To a Subset Of Ciliated Neurons And Are An Aspect Of Neuronal Functiomentioning
confidence: 99%
“…EVs isolated from C. elegans cultures when applied on wild‐type males induce a male mating behavior termed “tail‐chasing” (Silva et al., 2017; Wang et al., 2014). During mating, males deposit PKD‐2::GFP‐carrying EVs onto the vulva of the hermaphrodite, indicating that male‐derived EVs are targeted to specific locations on the hermaphrodite's body during the mating process (Wang et al., 2020).…”
Section: Extracellular Vesicle (Ev) Releasing Abilities Are Limited To a Subset Of Ciliated Neurons And Are An Aspect Of Neuronal Functiomentioning
confidence: 99%